TANTANGAN MENJADI GURU DI ERA DISRUPTIF - Handhini, Lidya Setio; Fitriyanti, Eka (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— Today, we oppose the industrial revolution known as the Industrial Revolution 4.0. This is an era of disrupted innovation, where innovation is developing very rapidly, so as to help create new markets. Facing great challenges, education is also required to be changed. Related to education at primary and secondary education levels. The era of education that was moved by the industrial revolution 4.0 was called Education 4.0. Indonesia is relatively slow in responding to the industrial revolution 4.0 compared to neighboring countries such as Malaysia and Singapore. The new 4.0 education system is developing this year. Therefore, the government must provide adequate facilities in welcoming the era of Education 4.0. As the front guard in the world of education, teachers must upgrade their competencies in facing the era of Education 4.0. Students who issue teachers today are millennials who are familiar with the digital world. Keywords— Teachers, Education, Disruptive Era Abstrak— Saat ini, kita menghadapi revolusi industri keempat yang dikenal dengan Revolusi Industri 4.0. Ini merupakan era inovasi disruptif, di mana inovasi ini berkembang sangat pesat, sehingga mampu membantu terciptanya pasar baru. Menghadapi tantangan yang besar tersebut maka pendidikan dituntut untuk berubah juga. Termasuk pendidikan pada jenjang pendidikan dasar dan menengah. Era pendidikan yang dipengaruhi oleh revolusi industri 4.0 disebut Pendidikan 4.0. Indonesia tergolong lambat dalam merespon revolusi industri 4.0 dibandingkan negara tetangga seperti Malaysia dan Singapura. Sistem pendidikan 4.0 baru bergaung kencang dalam tahun ini. Oleh karena itu, pemerintah harus menyediakan fasilitas yang memadai dalam menyongsong era Pendidikan 4.0. Sebagai garda terdepan dalam dunia pendidikan, guru harus meng-upgrade kompetensi dalam menghadapi era Pendidikan 4.0. Peserta didik yang dihadapi guru saat ini merupakan generasi milenial yang tidak asing lagi dengan dunia digital. Kata Kunci— Guru, Pendidikan, Era Disruptif